Dietary Beta-Hydroxy-Beta-Methyl Butyrate Supplementation Affects Growth, Carcass Characteristics, Meat Quality, and Serum Metabolomics Profile in Broiler Chickens - Tang, Zhiyi; Song, Bo; Zheng, Changbing; Zheng, Jie; Yin, Yulong; Chen, Jiashun (Frontiers in Physiology, 2021)
This study aimed to explore the effects of beta-hydroxy-beta-methyl butyrate (HMB) on serum metabolic profiles and meat quality of muscles in Wenshi broiler chickens. Birds were fed a basal diet with an additional 0, 0.05%, 0.10%, or 0.15% HMB, respectively. Results showed that dietary HMB quadratically increased the average daily gain (P = 0.058) and decreased feed:gain (P < 0.05) mainly in the starter phase. At 51 d of age, birds receiving 0.10% HMB diet exhibited less abdominal fat and more breast yield than the control (P < 0.05). Moreover, dietary HMB quadratically decreased the L* value and drip loss in selected muscles (P < 0.05), and increased the a* value in breast muscle (P < 0.05). Serum metabolome profiling showed that the most differentially abundant metabolites are lipids and lipid-like molecules, including phosphatidylcholines. It was concluded that HMB improved growth performance and meat quality of muscle in broilers.